THE EFFECTIVENESS OF ACCEPTANCE AND COMMITMENT THERAPY FOR SOCIAL ANXIETY DISORDER: Life Sciences-Psychology - BANAFSHEH GHARRAEE; KOMEIL ZAHEDI TAJRISHI; ABAS RAMAZANI FARANI; JAFAR BOLHARI; HOJJATOLLAH FARAHANI (International Journal of Life Science and Pharma Research, 2022)
One of the most common anxiety disorders is the Social Anxiety Disorder (SAD) which is characterized by intolerable anxiety and self-consciousness in daily social situations. Although a large body of study is conducted on the treatment for this disorder, further studies are required on new psychological therapies. The present study aims to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) on patients with SAD. The present randomized controlled trial(RCT) study is done along with pre-t est, post-test and follow-up with control group. Based on the Structured Clinical Interview for DSM (SCID), the 34 subjects who were prone to social anxiety disorder on the basis of DSM-5but had no other severe psychiatric disorders were distributed randomly and equally into experimental and control groups. The experimental group was treated with 12 weekly CFT sessions whereas the control group did not receive any treatment. In the initial phase of the research work especially after 12 weeks and after a followup period of 8 weeks, all subjects were evaluated with AAQ-II, MAAS, LOSC, SCS, WHOQOL-BREF and LSAS instruments. In addition to descriptive statistics, repeated measure analysis of variance (RM-ANOVA) was used in order to analyze the findings.Byusing SPSS-21 software, all analyses were conducted. Based on the RM-ANOVA, Acceptance and Commitment Therapy was found more effective than the control group in all of the studied variables in posttest and follow-up. All the observed differences between the two groups were significant (P < 0.01). Acceptance and commitment therapy (ACT) seems to play an essential role in reducing symptoms and in improving the quality of the life of patients with social anxiety disorder (SAD).